Fipronil, fenpropathrin and lambda cyhalothrin application alters defense related biomolecules composition favoring the resurgence of chilli thrips (Scirtothrips dorsalis) - T. Hemadri; M. Bheemanna; D. Srinivasa Reddy; Arunkumar Hosamani; R. Harischandra Naik; Saroja N. Rao; Nagaraj M. Naik; L. Rajesh Chowdary; Srikanth Barkeer; Keerthi Mc; B.L. Manisha; Wael Elmenofy; et al. (Journal of Asia-Pacific Entomology, 2026)

Development of methylcellulose/ZnO nanocomposite UV barrier coating to improve the shelf life of polyunsaturated fatty acid-rich oils - Ashique Thazheparamban; Mukul Kanakhara; Srikanth R. Veerabhadraiah; Arunkumar Panneerselvam (Food Packaging and Shelf Life, 2026)

Correction: Insect cypoviruses: advances in structural characterization, evolutionary genomics, and host interaction dynamics - Roja Gnanasekaran; Gangavarapu Subrahmanyam; Katsuhiko Ito; DSR Hiranmayi; Siripuk Suraporn; Luc Swevers; Joachim R. de Miranda; Himanshu Dubey; Rajal Debnath; Pawan Shukla; KP. Arunkumar; Liang Jiang; et al. (Archives of Virology, 2026)

A synergistic approach to water purification: SERS-assisted detection and nanofiltration of contaminants in natural rubber wastewater using graphene oxide noble-metal nanocomposites - I.Anushma Jeffrin; Arunkumar Selvam; R. Parimaladevi; Vasant Sathe; Mohamed A. Habila; Chih-Yu Kuo; M. Umadevi (Journal of Environmental Chemical Engineering, 2026)

Climatology of hailstorms over India (1994–2023): exploring trends and associations with thermodynamic indices - Bhavyasree; S. K. Panda; Unashish Mondal; Arunkumar R; Devesh Sharma; Someshwar Das (Natural Hazards, 2026)

Insect cypoviruses: advances in structural characterization, evolutionary genomics, and host interaction dynamics - Roja Gnanasekaran; Gangavarapu Subrahmanyam; Katsuhiko Ito; DSR Hiranmayi; Siripuk Suraporn; Luc Swevers; Joachim R. de Miranda; Himanshu Dubey; Rajal Debnath; Pawan Shukla; KP. Arunkumar; Liang Jiang; et al. (Archives of Virology, 2026)

Strategic considerations for nutrient use efficiency in sugarcane: Physiological, molecular and genetic perspectives - V. Krishnapriya; R. Manimekalai; R. Gomathi; Van Hay Duong; R. Arunkumar; P.T. Prathima; K. Devakumar; K. Thamilarasi; H.K. Mahadeva Swamy; Amaresh; P. Govindaraj; Prasanta K. Dash (Plant Science, 2026)

Eco-friendly synthesis of CuO nanoparticles using charcoal extract:Sustainable approach and mechanistic study of RhB dye degradation - M. Jothibas; B. Arunkumar; Abishake David Padmarajan; Kartheka Anandan; R. Sweet Stanly; Agalya Mathivanan; R. Piriyadharsini (Nanotechnology for Environmental Engineering, 2026)

Multi-trait index based Elucidation of drought tolerance potential of Saccharum spontaneum - T. Lakshmi Pathy; V. Vinu; R. Arunkumar; Gopalareddy Krishnappa; H. K. Mahadeva Swamy; R. Valarmathi; K. Dhanapal; Amaresh; P. Govindaraj; G. Hemaprabha; Bakshi Ram (Plant Physiology Reports, 2025)

Exploring the physiological mechanisms and ecofriendly mitigation strategies to combat the synergistic effects of drought and high temperature stress in Setaria italica - S. Gowsiga; D. Vijayalakshmi; J. Deepika; P. Arunkumar; R. Sivakumar; U. Sivakumar; V. Yamuna (Cereal Research Communications, 2025)

Testicular thermoregulation and blood perfusion score as markers of sperm quality in summer-stressed breeding bulls - D. Lakhanpal; T. K. Mohanty; M. Bhakat; R. Arunkumar; D. Nain; R. Baithalu (Tropical Animal Health and Production, 2025)

Green synthesis of silver nanoparticles using Ocimum sanctum for efficient Congo red dye removal: a response surface methodology approach - S. Murugeshwari; B. Senthil Rathi; N. Kalaiarasi; R. M. Saravana Kumar; I. Arunkumar; M. Vasanth; P. Senthil Kumar; Gayathri Rangasamy (Environmental Monitoring and Assessment, 2025)

Smart Water Management for SDG 6: A Review of AI and IoT-Enabled Solutions - Subhrajit Mandal; Anamika Yadav; Rishab Panwar; SM Shravan Kumar; Alagar Karthick; ArunKumar Priya; R. Vijayakumar; Sundaram Sankar Ganesh (Water Conservation Science and Engineering, 2025)

Effect of hybrid fiber and hybrid rebars on flexural strength of reinforced concrete beams - R. Rajkumar; Abhay Yadav; C. Arunkumar (Innovative Infrastructure Solutions, 2025)

Stilt floor optimization based on stiffness and column contribution - R. Kavitha; G. Keertiga; D. Suryakrishnan; N. Santhakrishnan; M. Arunkumar (Innovative Infrastructure Solutions, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Exploring potential biological applications of green derived silver nanoparticles using Codiaeum variegatum leaf extract - Arunkumar Lagashetty; M Anusha; Rachana; M Channabasavaraja; Shivakumar; V Veena; R․K Preeti; Sangappa K. Ganiger (Next Research, 2025)

First report of leaf spot disease on Zanthoxylum rhetsa caused by Fusarium solani-melongenae in India - N. Surmina Devi; T. Shantibala; Arunkumar Phurailatpam; N. Y. Chanu; Anju Choudhury; Priyanka Irungbam; P. Raja; R. C. Shakywar (Indian Phytopathology, 2025)

Study on cyclic behavior of concrete column steel beam connections - Madhu Paudel; C. Arunkumar; R. Rajkumar (Innovative Infrastructure Solutions, 2024)

Bacteria Normobiosis and Gracilaria edulis Growth; Metagenomic and Culture Studies Unfold New Insights on the Associated Bacterial Diversity - V. R. Umashree; Madangchanok Imchen; Ranjith Kumavath; Kulanthaiyesu Arunkumar (Thalassas: An International Journal of Marine Sciences, 2024)

Host seaweed extracts effect on epiphytic Acrochaetium sp growth and its phycobilipigments content and biological activity - V. R. Umashree; P. Dhanya; Kulanthaiyesu Arunkumar (Vegetos, 2024)

Multiscale teleconnection analysis of rainfall patterns over Calicut, India using wavelet coherence - S Adarsh; S Fathima; R Arunkumar (Journal of Earth System Science, 2024)

Mitigating abiotic stresses using natural and modified stilbites synergizing with changes in oxidative stress markers in aquaculture - D. Arunkumar; K. K. Krishnani; Neeraj Kumar; B. Sarkar; A. K. Upadhyay; P. B. Sawant; N. K. Chadha; R. Abisha (Environmental Geochemistry and Health, 2023)

Direct, indirect, post-infection damages induced by coronavirus in the human body: an overview - Sivan Padma Priya; P. M. Sunil; Sudhir Varma; Carel Brigi; Mohammad Faruq Abd Rachman Isnadi; J. A. Jayalal; R. Arunkumar Shadamarshan; S. Suresh Kumar; Neela Vasantha Kumari; Rishi P. R. Kumar (VirusDisease, 2022)

Retraction Note to: Methylation and Expression Patterns of Tropomyosin-Related Kinase Genes in Different Grades of Glioma - Mahalakshmi Palani; R. Arunkumar; Arrambakam Janardhanam Vanisree (NeuroMolecular Medicine, 2021)

Physiological traits imparting drought stress tolerance to promising sugarcane (Saccharum spp.) clones - R. Gomathi; V. Krishnapriya; R. Arunkumar; P. Govindaraj; Bakshi Ram (Plant Physiology Reports, 2020)

Life history, phenology, host range and natural enemies of Acria meyricki Shashank and Ramamurthy (Lepidoptera: Depressariidae): an emerging defoliator of oil palm, Elaeis guineenis Jacq. In India - L. Saravanan; P. Kalidas; T. Phanikumar; D. Dwarakakumar; Ankita Gupta; R. Arunkumar (Phytoparasitica, 2020)

Evaluating a multi-reservoir system for sustainable integrated operation using a simulation model - R. Arunkumar; V. Jothiprakash (Sustainable Water Resources Management, 2018)

Phosphorus dynamics and solubilizing microorganisms in acid soils under different land uses of Lesser Himalayas of India - Ranjan Paul; Raj Deo Singh; A. K. Patra; D. R. Biswas; Ranjan Bhattacharyya; K. Arunkumar (Agroforestry Systems, 2017)

RETRACTED ARTICLE: Methylation and Expression Patterns of Tropomyosin-Related Kinase Genes in Different Grades of Glioma - Mahalakshmi Palani; R. Arunkumar; Arrambakam Janardhanam Vanisree (NeuroMolecular Medicine, 2014)

Chaotic Evolutionary Algorithms for Multi-Reservoir Optimization - R. Arunkumar; V. Jothiprakash (Water Resources Management, 2013)

Characterization of mode of reproduction in Commiphora wightii [(Arnot) Bhandari] reveals novel pollen–pistil interaction and occurrence of obligate sexual female plants - K. A. Geetha; Aarti Kawane; Ashok Kumar Bishoyi; Arunkumar Phurailatpam; C. Ankita; S. K. Malik; R. Srinivasan; S. R. Bhat (Trees, 2013)

Optimization of Hydropower Reservoir Using Evolutionary Algorithms Coupled with Chaos - V. Jothiprakash; R. Arunkumar (Water Resources Management, 2013)

Development of Operational Policy for a Multi-reservoir System in India using Genetic Algorithm - V. Jothiprakash; Ganesan Shanthi; R. Arunkumar (Water Resources Management, 2011)

Quercetin downregulates matrix metalloproteinases 2 and 9 proteins expression in prostate cancer cells (PC-3) - M. R. Vijayababu; A. Arunkumar; P. Kanagaraj; P. Venkataraman; G. Krishnamoorthy; J. Arunakaran (Molecular and Cellular Biochemistry, 2006)